Regulating genome editing: for an enlightened democratic governance - Cavaliere, G; Devolder, K; Giubilini, A (Cambridge University Press, 2018)
How should we regulate genome editing in the face of persistent substantive disagreement about the moral status of this technology and its applications? In this paper, we aim to contribute to resolving this question. We first present two diametrically opposed possible approaches to the regulation of genome editing. A first approach, which we refer to as “elitist,” is inspired by Joshua Greene’s work in moral psychology. It aims to derive at an abstract theoretical level what preferences people would have if they were committed to implementing public policies regulating genome editing in a context of ethical pluralism. The second approach, which we refer to as the democratic approach, defended by Francoise Baylis and Sheila Jasanoff et al., emphasizes the importance of including the public’s expressed attitudes in the regulation of genome editing. After pointing out a serious shortcoming with each of these approaches, we propose our own favored approach—the “enlightened democracy” approach—which attempts to combine the strengths of the elitist and democratic approaches while avoiding their weaknesses.